The impact of the options backdating scandal on shareholders - Bernile, Gennaro; Jarrell, Gregg A. (Journal of Accounting and Economics, 2009)
The revelation that scores of firms engaged in the illegal manipulation of stock options’ grant dates (i.e. “backdating”) captured much public attention. The evidence indicates that the consequences stemming from management misconduct and misrepresentation are of first-order importance in this context as shareholders of firms accused of backdating experience large negative, statistically significant abnormal returns. Furthermore, shareholders’ losses are directly related to firms’ likely culpability and the magnitude of the resulting restatements, despite the limited cash flow implications. And, tellingly, the losses are attenuated when tainted management of less successful firms is more likely to be replaced and relatively many firms become takeover targets.